Ethical Considerations in Early Childhood Education: : Implication Of A Proffesional Responsibility - Magnesya, Wazabrilla Artha; Arifin, Imron; Putra, Yudithia Dian; Eny Nur Aisyah; Sulaiman, Alfarobi Ahmad (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
This study aims to describe the implementation of ethical considerations and professional responsibilities of educators in early childhood education. This research was conducted about 3 months at the end of the odd semester of the 2024/2025 school year at Dharma Wanita 2 Sawahan Kindergarten, Trenggalek, East Java, using a qualitative approach with a case study design. Data collection techniques include in-depth interviews, participatory observations, and school documentation, which are thethematically analyzed through data condensation, categorization, and conclusion drawn. The validity test of the data was carried out by member checks and extension of observations. The results of the study show that educators consider ethics reflectively by prioritizing the comfort, rights, and needs of children in the learning process. Teachers' professional responsibilities are reflected through open communication with parents, an empathetic attitude towards children, and dialogical problem solving. The applicable code of ethics not only serves as a written rule, but is also manifested in the school culture built through the example and support of the principal. This study recommends the integration of professional ethics materials into the Early Childhood Education teacher education curriculum and the strengthening of real-case based training so that teachers are able to make ethical decisions in daily practice. These findings are expected to be a reference for other Early Childhood Education institutions in forming an education system based on moral values and professional